Accuracy of the 14C-urea breath test for the diagnosis of Helicobacter pylori - Gomes, Ana Thereza Britto; Coelho, Luciano Kowalsky; Secaf, Marie; Módena, José Luiz Pimenta; Troncon, Luiz Ernesto de Almeida; Oliveira, Ricardo Brandt de (São Paulo Medical Journal, 2002)
CONTEXT: The development of simple, accurate and low-expense techniques for detection of Helicobacter pylori infection has great relevance. OBJECTIVE: To determine the accuracy of a rapid 14C-urea breath test (UBT) employing a very simple device for breathed air collection. DESIGN: Prospective study. SETTING: Hospital das Clinicas of the Faculty of Medicine of Ribeirão Preto. PARTICIPANTS: One hundred and thirty-seven adult patients who underwent upper gastrointestinal endoscopy in the Clinical Hospital. MAIN MEASUREMENTS: Histology for Helicobacter pylori (HP); urease test; urea breath test (UBT). RESULTS: One hundred and fifteen patients were infected by HP (HP+) according to both histology and the urease test, and 22 patients were HPnegative (HP-), according to the same two tests. UBT was capable of discriminating between HP+ and HP- in a way that was similar to the combination of urease test and histology. When this combination of results is taken as the “gold standard” for HP infection, the sensitivity and specificity of UBT are both greater than 90% for a range of cut-off points and breathed air collection times. CONCLUSION: The rapid UBT employing a simple device for air collection has a high accuracy in determining HP infection.